Dependence of memory characteristics on the (ZrO2)x(SiO2)1−x elemental composition for charge trap flash memory applications. (18th May 2015) - Tang, Zhenjie; Lu, Xubing; Yang, Yupeng; Zhang, Jing; Ma, Dongwei; Li, Rong; Zhang, Xiwei; Hu, Dan; Li, Tingxian
Abstract: Charge trap flash memory capacitors incorporating various (ZrO2 ) x (SiO2 )1− x films ( x  = 1.0, 0.92, 0.79, 0.63, 0.46, 0.28, 0.17 and 0.08) as the charge trapping layer were fabricated, and the dependence of the memory window, data retention and program/erase speed on the mole fraction value x were investigated. It was observed that changing the elemental composition affects the dielectric constant and equivalent oxide thickness of (ZrO2 ) x (SiO2 )1− x films, and the memory capacitor ( x  = 0.63) exhibits a memory window as large as 10.7 V for a ±10 V sweeping voltage range, and a low extrapolated charge loss of 9.0% over a period of 10 years. A faster program/erase speed can be obtained for memory capacitors when x  = 0.79 and 0.63. The results should be attributed to the different (ZrO2 ) x (SiO2 )1− x microstructures, defect state densities and energy band alignments resulting from the change of compositions. In order to achieve the trade-off between the memory window, data retention, and program/erase speed, the optimal x values of the (ZrO2 ) x (SiO2 )1− x trapping layer are in the range of 0.63 to 0.79 for charge trap flash memory applications. The present study provides useful insights for the composition selection for a complex oxide-based charge trap flash memory.